THE ROLE OF ASSET MANAGEMENT IN THE OPERATION AND MAINTENANCE OF POWER TRANSFORMERS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
This paper presents an analysis of the application of the asset management concept to the operation of power transformers. It presents the main elements underlying the efficient management of these assets, starting with continuous monitoring of their technical condition, which is essential for the early identification of defects and the prevention of major incidents. Particular emphasis is placed on determining the Health Index for each transformer, a method that enables objective assessment of its actual condition and reduces uncertainties associated with operational decisions. Based on this index, transformers can be ranked and prioritized by risk, criticality, and investment needs, thereby facilitating optimal planning for maintenance, upgrades, and replacements.The paper also presents how these elements converge within an integrated asset management concept that aims to maximize transformer service life, reduce operating costs, and increase network reliability. In conclusion, adopting a modern asset management model is a necessary condition for ensuring an efficient balance among performance, risk, and cost in the operation of power transformers.
Keywords: Asset Management; Power Transformers; Online Monitoring; Offline Monitoring